An Investigation into the Role of Tourism Growth, Conventional Energy Consumption and Real Income on Ecological Footprint Nexus in France - Marymagdaline Enowmbi Tarkang; Fetus Fatai Adedoyin; Festus Victor Bekun (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Previously documented studies in the literature on how tourism leads to economic growth in the form of tourism-led growth hypotheses (TLGH) has been investigated. This study presents a new perspective on the growth of tourism by considering its impact on conventional energy consumption, real income level, and emission via the channel of globalization. Sequences of econometric tests were conducted to validate the hypothesized claims between tourism development and growth impact on conventional energy consumption and pollution proxy by ecological footprints, globalization GDP per capita, biocapacity, and tourists for the case of France. Empirical evidence from the Granger causality test presents a uni-directional causality from ecological footprints to GDP per capita and from biocapacity to ecological footprints. The correlation matrix shows interrelation amongst series with biocapacity significantly correlating with ecological footprints with tourist’s arrival having a positive correlation with ecological footprints and a negative one with biocapacity. GPD per capita was found to positively affect the ecological footprints and have a negative correlation with biocapacity and a significant relationship with tourists' arrivals. Additionally, globalization exerts a positive impact on ecological footprints, and its effect on biocapacity was found to be negative although globalization's effect on tourists’ arrivals and per capita GDP is significant. The ARDL estimation indicated biocapacity as a neutral agent for ecological footprints, tourist arrivals having a negative impact on ecological footprints, and globalization significantly affecting ecological footprints. From these findings, it is evident that tourism growth has a significant impact on energy consumption and pollution. Policy recommendations were also provided in this study accordingly.